THE CONCEPTUAL FIELD OF LOVE IN THE ITALIAN, SPANISH AND SERBIAN LANGUAGE PHRASEOLOGISM THAT CONTAIN A COMPONENT EYE (Živi jezici: Journal for Foreign Languages and Literatures, 2023)
The paper deals with contrasting idioms with the component eye in Italian, Spanish and Serbian, with the aim of establishing identities, similarities and differences at the interlingual level. Considering the high phraseological potential of the somatic lexeme, the research was limited to only one conceptual field - love. The research is conducted with the aim of determining whether the members of two linguistic and cultural communities that speak typologically similar languages (Italian and Spanish) will conceptualize phenomena in a more similar way than do the members of the Serbian linguistic and cultural community whose language is typologically distant. The initial hypothesis was that genetically closely related languages would share more common phraseological features than genetically unrelated languages. In order to conduct the research, a corpus was excerpted from general and phraseological dictionaries, and then it was subjected to contrastive and conceptual analysis. The results show that members of the Italian and Spanish linguistic and cultural communities conceptualize love in a more similar way in their somatisms, but also that the Serbian phraseological fund contains a significant number of cases of absolute elvivalence, as a result of the common European origin of idioms, calquing or polygenesis.
Keywords: contrastive phraseology, equivalence, love, eye, Italian, Spanish, Serbian